2009
DOI: 10.1097/ijg.0b013e31817eee0b
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Selective Laser Trabeculoplasty

Abstract: Purpose-To evaluate the efficacy of repeat 360° selective laser trabeculoplasty (SLT) in glaucoma patients with prior successful 360° SLT. Design-Retrospective chart reviewMethods-Forty-four eyes of 35 patients, ≥ 18 years of age, with open-angle glaucoma (primary open-angle, pseudoexfoliation or pigmentary glaucoma), uncontrolled on maximum tolerable medical therapy, underwent an initial 360° SLT (SLT1), which was successful for ≥ 6 months, but eventually lost efficacy and was followed by a repeat 360° SLT (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 7 publications
2
84
1
1
Order By: Relevance
“…At 12 months, threequarters of patients continued to do well without the need for medical therapy. Regarding repeatability of SLT, to our knowledge, the only peer-reviewed published data to date is from Hong and colleagues, 23 who reported that success of second SLT (Ն20% IOP reduction) was comparable to that of first SLT in a retrospective analysis. No ethnicity data were provided in that study, shedding no light on the repeatability of SLT in people of African descent.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…At 12 months, threequarters of patients continued to do well without the need for medical therapy. Regarding repeatability of SLT, to our knowledge, the only peer-reviewed published data to date is from Hong and colleagues, 23 who reported that success of second SLT (Ն20% IOP reduction) was comparable to that of first SLT in a retrospective analysis. No ethnicity data were provided in that study, shedding no light on the repeatability of SLT in people of African descent.…”
Section: Commentmentioning
confidence: 99%
“…16,17 Selective laser trabeculoplasty (SLT) is equally safe and effective as ALT, [18][19][20][21][22] is more portable than argon-based laser platforms, and a recent published study suggested that SLT may be safe and effective when repeated after the initial treatment effect wanes. 23 Selective laser trabeculoplasty meets many of the criteria necessary for viable application in the developing world: the treatment is fast, safe, and minimally invasive, and no postoperative medications or evaluations are strictly necessary; the equipment is portable; and the incremental cost of treatment is small once the equipment and expertise are onsite. Selective laser trabeculoplasty has also not been widely applied to glaucoma management in the developing world, likely for all the reasons previously enumerated here for ALT and also because-unlike the argon laser system-the SLT system is a dedicated device with a single indication.…”
mentioning
confidence: 99%
“…Looking close at the more recent literature, one can note several studies showing that SLT can be repeated with similar efficacy when compared to the first SLT treatment. In these studies, POAG patients presented a significant IOP reduction at 1 (46) , 4 (47) , 6 (46) , 12 (19,48) , 15 (46) , and 24 months after repeating SLT (26,49) . Corroborating these findings, Gandolfi and Ungaro demonstrated that repeated low power SLT as initial treatment postponed the initiation of medical therapy by a mean time of 6.2 years in patients with OHT (19) .…”
Section: Safety Duration and Repeatabilitymentioning
confidence: 99%
“…With this in mind, we believe it is reasonable to consider alternative treatments, such as laser therapy, as first-line treatment options (17,28,29) . SLT has a good safety profile, does not rely on patient compliance, and has shown to be at least as effective as topical medications in lowering IOP as an initial treatment (for at least one year) (70)(71)(72) and can be repeated when IOP control is lost over time (19,(46)(47)(48) , possibly allowing patients to remain free of topical medication for years (73,74) . In a chronic disease such as OAG, time is always a key parameter.…”
Section: Commentmentioning
confidence: 99%
“…They found that repeating SLT is effective in reducing intraocular pressure. The mean intraocular pressure reduction at 8 months after the first and second procedure did not significantly differ, being 4 mmHg and 2.9 mmHg, respectively (Hong et al, 2009). …”
Section: Is Slt Repeatable?mentioning
confidence: 99%